Religious Crisis as an Independent Causal Predictor of Psychological Distress: Understanding the Unique Role of the Numinous for Intrapsychic Functioning - Fox, Jesse (Religions, 2020)
Religious and spiritual (R/S) struggles are tensions or conflicts one experiences in relationship to what is considered sacred or transcendent. In this study, we tested competing causal models of psychological distress as it relates to personality and R/S struggle using structural equation modeling. The study sample consisted of 226 (72.0%) females and 88 (28.0%) males (n = 314) drawn from the Amazon’s Mechanical Turk (MTurk) worker population. We found that though the five-factor model (FFM) of personality was a robust predictor of psychological distress, the R/S struggle added significant, incremental predictiveness. SEM analyses supported our contention that R/S struggle may represent a new, causal pathway of psychological distress that is independent from the FFM. Our findings are taken as evidence that R/S struggles require unique ways of conceptualizing their causal impact on clinical impairment and that psychological interventions need to systematically address numinous constructs in order to ensure that all aspects of emotional dysphoria are considered and their influences treated.